Lubricating coating prepared by PIIID on a forming tool - Martinatti, J. F. [UNESP]; Santos, L. V.; Durrant, S. F. [UNESP]; Cruz, N. C. [UNESP]; Rangel, E. C. [UNESP] (Iop Publishing Ltd, 2012)
In this work, the performance of a-C: H films produced by the hybrid Plasma Immersion Ion Implantation and Deposition technique as lubricating layers for a steel forming tool has been investigated. Hardened steel (AISI M2, 64 HRC) plates coated with a commercial TiN layer were used as substrates and the films were deposited in a vacuum chamber fitted with two parallel-plate electrodes. The discharges were generated in atmospheres composed of 91% C2H2 and 9% Ar by the application of radiofrequency power (13.56 MHz, 100 W) to the upper electrode while the lower one, also used as the sample holder, was biased with high voltage negative pulses (3.6 kV, 30 mu s, 300 Hz). A deposition time of 840 s was used. The effects of the gas pressure, p, on thickness, molecular structure, wettability, surface morphology and topography, hardness and friction coefficient of the films lwere investigated. Film thickness increased from 0.3 to 0.5 mu m when p was increased from 2.7 to 16.5 Pa. Generally, the films were slightly hydrophilic, with contact angles of around 84 degrees, and the deposition decreased the roughness of the steel. A polymer-like structure was detected in high pressure depositions and an amorphous carbon structure derived from the low pressure procedures. Hardness decreased from 8.2 to 7.0 GPa with increasing p. Improvement in tribological performance was indicated by the fall in the friction coefficient from 0.5 to 0.2 as the deposition pressure was reduced. Operating at the latter value (of mu) would lead to a significant reduction in wear and hence to significant economy in diverse industrial applications.